2020
DOI: 10.1111/1759-7714.13559
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of D‐dimer in non‐small cell lung cancer patients receiving radical surgery and its association with postoperative venous thromboembolism

Abstract: Background Venous thromboembolism (VTE) occurs at a high rate after lung cancer surgery and can be attributed to various clinical risk factors. Here, we aimed to determine whether early detection of perioperative D‐dimer and risk‐stratified cutoff values would improve the diagnostic efficacy of VTE. Methods In this case‐control study, D‐dimer results were acquired from 171 non‐small cell lung cancer (NSCLC) patients preoperatively and at the first, third, and fifth day after surgery. VTE was confirmed by Doppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Although D-dimer is affected by many factors, it is still considered as a most powerful indicator of venous thromboembolic events. 23 , 24 Owings et al 25 sampled the plasma of severely injured patients for D-dimer assay at hours 8, 16, 24, and 48; and at days 3, 4, 5, and 6. they found before 48 h after injury, the vast majority of patients without thromboembolism had positive D-dimer assays, and D-dimer levels might be very low within 48 h of injury. Our previous study found that in patients with thoracolumbar fractures caused by high-energy injuries, D-dimer at admission was a risk factor for DVT, but the AUC value was not very high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although D-dimer is affected by many factors, it is still considered as a most powerful indicator of venous thromboembolic events. 23 , 24 Owings et al 25 sampled the plasma of severely injured patients for D-dimer assay at hours 8, 16, 24, and 48; and at days 3, 4, 5, and 6. they found before 48 h after injury, the vast majority of patients without thromboembolism had positive D-dimer assays, and D-dimer levels might be very low within 48 h of injury. Our previous study found that in patients with thoracolumbar fractures caused by high-energy injuries, D-dimer at admission was a risk factor for DVT, but the AUC value was not very high.…”
Section: Discussionmentioning
confidence: 99%
“…When employing D-dimer, many studies have taken various measures to improve the diagnostic value of D-dimer. 23 , 31 , 32 Ke et al used a respective cut-off value of D-dimer in subgroups and elevated the diagnostic ability of D-dimer in lung cancer patients after surgery. 23 In the present study, we performed a separate ROC analysis in order to determine the cut-off value in subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse events concerning bleeding included major bleeding that required surgical or endoscopic hemostasis or blood transfusion, and minor bleeding that required either discontinuation of drug treatment or drug hemostasis. All results were evaluated on the first, third, and fifth days after surgery, because a previous study found that fluctuations in D-dimer levels were generally significant during the first five days after lung resection (20).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the adapted Caprini scores were calculated in the early days postoperatively to incorporate clinical variables that displayed instant changes after surgery, while detecting the emergence of new risk factors (e.g., confined to bed over 72 h). Among them, D-dimer concentration is the very one that increases constantly the following surgery in a short time, 46 which means that the derived scores can be different at different time points. However, Alexander et al 47 found that even thrombosis biomarkers profiles including D-dimer concentration changed over time, the accompanied dynamic thrombogenic risks were not significantly associated with reliably discriminatory predictability of VTE event within a short period of following time (in 30 days).…”
Section: Multivariate Regression Analysis Was Performed By Incorporatingmentioning
confidence: 99%